2001
DOI: 10.1093/oxfordjournals.rpd.a006549
|View full text |Cite
|
Sign up to set email alerts
|

Entrance Surface, Organ and Effective Doses for some of the Patients Undergoing Different Types of X Ray Procedures in Bangladesh

Abstract: Entrance surface doses (ESDs) were measured for the most common types of X ray procedures, such as chest PA, lumber spine AP, lumber spine lateral, skull AP, skull lateral and pelvis AP in four major hospitals of Dhaka, the capital city of Bangladesh. Organ/tissue doses for 29 organs/tissues and effective doses for the patients were also calculated using the entrance surface dose as the input quantity. Organ/tissue doses and effective doses were calculated by using XDOSE software based on the Monte Carlo compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…The generators were matched as much as possible for the combination conditions of mAs, kvp, type of amplifier sheets, and daily work load in the hospitals, so the measurements would not be biased by these factors [15].…”
Section: Methodsmentioning
confidence: 99%
“…The generators were matched as much as possible for the combination conditions of mAs, kvp, type of amplifier sheets, and daily work load in the hospitals, so the measurements would not be biased by these factors [15].…”
Section: Methodsmentioning
confidence: 99%
“…In figure 4(a-c), a comparison is established between the average ESD, ESAK and exposure factor values obtained in this study and the ESD values reported in previous studies from India (24) , Korea (25) , Iran (26) , the United Kingdom (UK) (27) , Malaysia (28) , Switzerland (29) , Bangladesh (30) , Bulgaria (31) , Italy (32) , Sudan (33) , Nigeria (34) , Lithuania (35) and Russia (36) . It can be observed that the mean ESD values of the skull LAT exami- nation in this study were higher than those reported in the UK (27) but less than those in several other countries (24,(28)(29)(30)(31)(34)(35)(36) . In this study, we chose to compare our mean ESD values with the internationally reported dose metrics, but the recent recommendations favour median values.…”
Section: Discussionmentioning
confidence: 76%
“…While, the value of ESD measured at this study was significantly greater than those recorded in some other countries such as the United States,[10] Greece,[1112] Brazil,[13] and Bangladesh. [14] In Greece, the mean values of ESD were found to be 0.044 mGy for chest PA and 0.043 mGy for chest LAT. In Brazil mean values of ESD for PA and LAT projections were 0.22 and 0.98 mGy, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While in the United States,[10] Greece,[1112] Brazil,[13] and Bangladesh[14] investigations showed that patients dose from common X-ray examination were below the ICRP reference doses.…”
Section: Introductionmentioning
confidence: 99%